2017
DOI: 10.1002/2016gb005557
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns of woody residence time and its influence on model simulation of aboveground biomass

Abstract: Running Title: forest woody residence time and biomass modeling Key Points:(1) Woody residence time (τ w , years) is related to forest age, annual temperature and precipitation.(2) Influences of meteorological drivers on τ w are different among various plant functional types.(3) The estimated global forest τ w shows large spatial heterogeneity and this strongly AbstractWoody residence time (τ w ) is an important parameter that expresses the balance between mature forest recruitment/growth and mortality. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 67 publications
(113 reference statements)
0
14
1
1
Order By: Relevance
“…In addition, the vegetation C partition scheme varies with stand age (Zhou, Shi, et al., ). The decisive role of whole‐vegetation turnover time in determining the uncertainty in ecosystem C storage capacity has been supported by recent modeling and experimental research (Friend et al., ; Medlyn et al., ; Xue et al., ). Therefore, our results further highlight the need to focus on the deviation in vegetation C turnover time under the SSA to avoid considerable bias in ecosystem MTT and thus the C sequestration estimation.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the vegetation C partition scheme varies with stand age (Zhou, Shi, et al., ). The decisive role of whole‐vegetation turnover time in determining the uncertainty in ecosystem C storage capacity has been supported by recent modeling and experimental research (Friend et al., ; Medlyn et al., ; Xue et al., ). Therefore, our results further highlight the need to focus on the deviation in vegetation C turnover time under the SSA to avoid considerable bias in ecosystem MTT and thus the C sequestration estimation.…”
Section: Discussionmentioning
confidence: 91%
“…Most of the current DGVMs use a fixed turnover rate (or mortality rate) for wood biomass and they do not explicitly simulate tree mortality attributable to factors such as fire, competition, insects and pathogens. A few exceptions (e.g., LPJ and LPJ‐GUESS models) do not use a simple fixed value, and they calculate the mortality rate attributable to negative carbon balance, competition, harsh climate and fire (Xue et al., 2017). Our gridded turnover time/rate of carbon pools might help to improve model structure or parameterization schemes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is useful to compute the carbon allocation and turnover time of individual pools separately. At the plot level, carbon allocation and turnover time within the major carbon pools have been measured (Chen et al., 2013; Keeling & Phillips, 2007; Xue et al., 2017), but information on large‐scale patterns of carbon allocation and turnover is still lacking. Moreover, using tree‐ring data or ground measurements, previous studies found a trade‐off between the growth and the life span of trees (Brienen et al, 2020; Stephenson & van Mantgem, 2005), but it still remains unknown whether the hypothesis of “grow fast, die fast” holds good at the ecosystem scale.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as a carbon sink, forest dynamics are closely related to the global carbon cycle and climate changes [2][3][4]. Canopy height is an important forest structure parameter for understanding the forest ecosystem, and has been used to estimate forest aboveground biomass and therefore model the global carbon stock and carbon dynamics [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%